Sex differences in lifetime risk and first manifestation of cardiovascular disease: prospective population based cohort study. (17th November 2014) - Leening, Maarten J G; Ferket, Bart S; Steyerberg, Ewout W; Kavousi, Maryam; Deckers, Jaap W; Nieboer, Daan; Heeringa, Jan; Portegies, Marileen L P; Hofman, Albert; Ikram, M Arfan; Hunink, M G Myriam; Franco, Oscar H; et al.
Abstract : Objective To evaluate differences in first manifestations of cardiovascular disease between men and women in a competing risks framework. Design Prospective population based cohort study. Setting People living in the community in Rotterdam, the Netherlands. Participants 8419 participants (60.9% women) aged ≥55 and free from cardiovascular disease at baseline. Main outcome measures First diagnosis of coronary heart disease (myocardial infarction, revascularisation, and coronary death), cerebrovascular disease (stroke, transient ischaemic attack, and carotid revascularisation), heart failure, or other cardiovascular death; or death from non-cardiovascular causes. Data were used to calculate lifetime risks of cardiovascular disease and its first incident manifestations adjusted for competing non-cardiovascular death. Results During follow-up of up to 20.1 years, 2888 participants developed cardiovascular disease (826 coronary heart disease, 1198 cerebrovascular disease, 762 heart failure, and 102 other cardiovascular death). At age 55, overall lifetime risks of cardiovascular disease were 67.1% (95% confidence interval 64.7% to 69.5%) for men and 66.4% (64.2% to 68.7%) for women. Lifetime risks of first incident manifestations of cardiovascular disease in men were 27.2% (24.1% to 30.3%) for coronary heart disease, 22.8% (20.4% to 25.1%) for cerebrovascular disease, 14.9% (13.3% to 16.6%) for heart failure, and 2.3% (1.6% to 2.9%) for other deaths from cardiovascular disease. For women the figures were 16.9% (13.5% to 20.4%), 29.8% (27.7% to 31.9%), 17.5% (15.9% to 19.2%), and 2.1% (1.6% to 2.7%), respectively. Differences in the number of events that developed over the lifespan in women compared with men (per 1000) were −7 for any cardiovascular disease, −102 for coronary heart disease, 70 for cerebrovascular disease, 26 for heart failure, and −1 for other cardiovascular death; all outcomes manifested at a higher age in women. Patterns were similar when analyses were restricted to hard atherosclerotic cardiovascular disease outcomes, but absolute risk differences between men and women were attenuated for both coronary heart disease and stroke. Conclusions At age 55, though men and women have similar lifetime risks of cardiovascular disease, there are considerable differences in the first manifestation. Men are more likely to develop coronary heart disease as a first event, while women are more likely to have cerebrovascular disease or heart failure as their first event, although these manifestations appear most often at older ages.